1999
DOI: 10.1080/08035259950169396
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal enuresis: a suggestion for a European treatment strategy

Abstract: The objective of this study was to review the published literature on aetiology and treatment of nocturnal enuresis, with the aim of providing a treatment strategy which is easy for the patient and their family to follow. Results from European studies conducted over the last 15 y were included in this review. It can be concluded from the results of these studies that enuresis is the cause and not the result of a psychiatric disorder. However, there is still considerable variation in success rates, from 28 to 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
50
0
7

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 51 publications
(70 reference statements)
0
50
0
7
Order By: Relevance
“…Despite the high incidence, a few studies have addressed the pathophysiology of NE [5,6]. Several pathophysiological mechanisms have been proposed [7], e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high incidence, a few studies have addressed the pathophysiology of NE [5,6]. Several pathophysiological mechanisms have been proposed [7], e.g.…”
Section: Introductionmentioning
confidence: 99%
“…PNE is thought to be caused by reduced nocturnal bladder capacity, nocturnal polyuria, awakening problem or a combination of these factors (Hunsballe et al, 1995;Loening-Baucke, 1997;Wolfish et al, 1997;Lackgren et al, 1999;Kawauchi et al, 2002). Also genetic susceptibility, constipation and hypercalciuria have been attributed to the etiology of PNE whereas psychosocial factors, urinary tract infections, constipation, diabetes, neurogenic bladder are reported as causes of SNE (Pace et al, 1999;Robson and Leung, 2000;Sureshkumar et al, 2000;Raes et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first choice of therapy should be the one most acceptable to the whole family [1]and due to the lack of a prospective randomized trial comparing the alternative option using laser acupuncture with the well–established desmopressin therapy, we performed an ethical committee approved study. Some single studies on different forms of acupuncture, either using needles or electrostimulation, showed surprinsingly high success rates of up to 98.2% [8, 9, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Modern classification divides the affected children into several subgroups, according to history, symptom pattern, presence of nocturnal polyuria, and response to treatment with the vasopressin analogue desmopressin [1]. This paper refers to the specific subgroup of children suffering from primary nocturnal enuresis with normal daytime voiding patterns and high nighttime urine production.…”
Section: Introductionmentioning
confidence: 99%